Therapeutic drug monitoring of lacosamide among children: is it helpful? - Kohn, Elkana; Lezinger, Mirit; Daniel, Sharon; Masarwi, Majdi; Brandriss, Nurit; Bar-Chaim, Adina; Berkovitch, Matitiahu; Heyman, Eli; Komargodski, Rinat (Frontiers in Pharmacology, 2023)
Objective: This study aimed to investigate the efficacy and tolerability of Lacosamide (LCM) in a pediatric population with refractory epilepsy in relation to serum concentration, age, and dosage. Methods: Demographic and clinical data were collected from the medical records of children with refractory epilepsy treated with LCM at Shamir Medical Center between February 2019 to September 2021, in whom medication blood levels were measured. Trough serum LCM concentration was measured in the biochemical laboratory using High-Performance Liquid Chromatography (HPLC) and correlated with the administered dose and clinical report. Results: Forty-two children aged 10.43 ± 5.13 (range: 1-18) years old were included in the study. The average daily dose of LCM was 306.62 ± 133.20 mg (range: 100-600). The average number of seizures per day was 3.53±7.25 compared to 0.87±1.40 before and after LCM treatment, respectively. The mean LCM serum concentration was 6.74±3.27 mg/l. No statistically significant association was found between LCM serum levels and the clinical response (p=0.58), as well as the correlation between LCM dosage and the change in seizure rate (p=0.30). Our study did not find a correlation between LCM serum concentration and LCM dosage and the gender of the participants: males (n=17,) females (n=23) (p=0.31 and p=0.94, respectively). A positive trend was found between age and LCM serum concentrations (r=0.26, p=0.09). Conclusion: Determination of serum concentrations is not needed in all children treated with LCM. Serum concentrations may be valuable in patients with refractory epilepsy for compliance evaluation or in patients with satisfactory control of seizures to determine their therapeutic baseline.